Local Awareness in Making Social Integration of Society at Mendahara District - Syafutra, Satria; Montessori, Maria; Suhono, Suhono (Graduate Program Magister Manajemen Pendidikan, 2021)
The pluralistic Indonesian society has different systems and regulations from one region to another. This pluralistic area makes Indonesia diverse in terms of religion, ethnicity, and culture. A mature society forms integration in its society. Integration that was born to reduce conflicts between different communities. This study aims to find local wisdom that is still maintained in society so that social integration is well established. This research is in the form of a case study using descriptive qualitative methods. The subjects of this research are the people in Mendahara District. Taking the subject of this study using purposive sampling. Techniques for ensuring the validity of data are carried out by fostering familiarity with subjects and informants, persistence of observation and triangulation. Data analysis techniques used by researchers are data reduction, data display and conclusion drawing and verification. The findings of this study indicate that the local wisdom of the people of Mendahara District has its own binding to the community, where the community obeys the traditions left by their ancestors. The people of Mendahara District form reciprocal relationships between existing ethnicities, the values of ancestral culture are still very closely held by the people of Mendahara District.